(untitled) (African Journal of Biomedical Research, 2024)
The objectives of this study were to determine the knowledge of pharmacists regarding chronic kidney disease and to determine the impact of socio-demographic characteristics on pharmacists’ knowledge as well as to determine the impact of educational intervention on pharmacists’ knowledge of chronic kidney disease. The study was a prospective, cross-sectional interventional study undertaken in the Department of Pharmacy, Federal Medical Centre Asaba and the Department of Pharmacy Delta State University Teaching Hospital Oghara, as well as in all the Central hospitals in the State for over a period of one year. Data collection was done using the kidney knowledge survey (KIKS) 28-items questionnaire. The data on the retrieved copies of the questionnaire were analyzed with Statistical Package for Social Sciences version 20. The average knowledge of the respondents in the various centers surveyed was good. There was no statistically significant difference in the overall mean knowledge score between the centers p>0.05. However, DELSUTH Oghara had a higher overall mean score of 21.89±3.01 (78.2%), followed by Federal Medical Center Asaba 20.41±2.61 (72.9%) and Central hospitals 19.40±3.72 (69.3%). Socio demographics had no impact on the average knowledge of the pharmacists. The intervention programme impacted positively on pharmacists’ knowledge of chronic kidney disease.